Hunters' responses to chronic wasting disease: specialization, social trust, and perceived risk - Needham, Mark David, author; Vaske, Jerry J., advisor; Donnelly, Maureen P., committee member; Manfredo, Michael J., committee member; Benson, Delwin E., committee member (Colorado State University. Libraries, 2006)
Chronic wasting disease (CWD) is found in deer, elk, and moose in several states and provinces. CWD causes abnormal behavior, emaciation, and death in all infected animals. Although CWD has not caused human health problems, transmission to humans cannot be dismissed. Little is known about the extent to which hunters: (a) would hunt in other states or quit hunting in response to CWD and whether this behavior differs among subgroups of hunters, and (b) perceive personal risks from CWD and the influence of trust in wildlife agencies as a determinant of risk. This dissertation presents three articles that address these knowledge gaps using data from surveys (n = 9,567) of resident and nonresident deer and elk hunters in eight states. Hunters were presented with hypothetical scenarios of CWD prevalence and human risks. The first article shows that at current prevalence levels, few hunters would change behavior. As conditions worsen (e.g., 50% prevalence, human death), up to 18% would switch states and 37% would quit. Residents were likely to quit; nonresidents would switch states. Arizona and North Dakota hunters were most likely to change behavior. Given that CWD is not found in these states, it may pose a new risk. In Wisconsin, where hunting is a tradition, hunters were least likely to change behavior. CWD testing and herd reduction were acceptable; taking no action was unacceptable. The second article examines responses to these scenarios among subgroups of hunters based on their specialization. Cluster analysis revealed four specialization groups (casual, intermediate, focused, veteran). Casual hunters were most likely to quit; veterans were least likely. Veteran residents were most likely to switch states; casual residents were least likely. For nonresidents, there were few differences among specialization groups regarding intention to switch states. The third article shows that hunters trusted agencies to manage CWD, but still perceived risk from the disease. Structural equation models showed that perceptions of similarity positively influenced trust, explaining up to 49% of the variance in trust. Hunters who trusted agencies perceived less CWD risk, but trust only explained up to 8% of the variance in risk. Research and management implications are discussed.
Keywords: recreation; forestry; social psychology